Electronic health records in Brazil: Prospects and technological challenges - Barbalho, Ingridy M. P.; Fernandes, Felipe; Barros, Daniele M. S.; Paiva, Jailton C.; Henriques, Jorge; Morais, Antônio H. F.; Coutinho, Karilany D.; Coelho Neto, Giliate C.; Chioro, Arthur; Valentim, Ricardo A. M. (Frontiers in Public Health, 2022)
Electronic Health Records (EHR) are critical tools for advancing digital health worldwide. In Brazil, EHR development must follow specific standards, laws, and guidelines that contribute to implementing beneficial resources for population health monitoring. This paper presents an audit of the main approaches used for EHR development in Brazil, thus highlighting prospects, challenges, and existing gaps in the field. We applied a systematic review protocol to search for articles published from 2011 to 2021 in seven databases (Science Direct, Web of Science, PubMed, Springer, IEEE Xplore, ACM Digital Library, and SciELO). Subsequently, we analyzed 14 articles that met the inclusion and quality criteria and answered our research questions. According to this analysis, 78.58% (11) of the articles state that interoperability between systems is essential for improving patient care. Moreover, many resources are being designed and deployed to achieve this communication between EHRs and other healthcare systems in the Brazilian landscape. Besides interoperability, the articles report other considerable elements: i) the need for increased security with the deployment of permission resources for viewing patient data, ii) the absence of accurate data for testing EHRs, and iii) the relevance of defining a methodology for EHR development. Our review provides an overview of EHR development in Brazil and discusses current gaps, innovative approaches, and technological solutions that could potentially address the related challenges. Lastly, our study also addresses primary elements that could contribute to relevant components of EHR development in the context of Brazil's public health system.